2019 IEEE 12th International Conference on Cloud Computing (CLOUD) 2019
DOI: 10.1109/cloud.2019.00095
|View full text |Cite
|
Sign up to set email alerts
|

Towards Scalable k-out-of-n Models for Assessing the Reliability of Large-Scale Function-as-a-Service Systems with Bayesian Networks

Abstract: Typically, Function-as-a-Service (FaaS) involves state-less replication with very large numbers of instances. The reliability of such services can be evaluated using Bayesian Networks and k-out-of-n models. However, existing k-out-of-n models do not scale to the larger number of hosts of FaaS services. Therefore, we propose a scalable k-out-of-n model in this paper with the same semantics as the standard k-out-of-n voting gates in fault trees, enabling the reliability analysis of FaaS services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…To use the k/n voting gate in settings as they occur in current large-scale systems, where we have large sets of redundant server clusters, we provide a scalable BN representation of the k/n voting gate. This work is based on our previous work [27], where we showed that the scalable k/n model can be built with the temporal noisy adder by Heckerman [24]. The BN model of the noisy adder is a random variable representing a counter and a probability distribution that defines the likelihood of observing a certain count.…”
Section: Introductionmentioning
confidence: 99%
“…To use the k/n voting gate in settings as they occur in current large-scale systems, where we have large sets of redundant server clusters, we provide a scalable BN representation of the k/n voting gate. This work is based on our previous work [27], where we showed that the scalable k/n model can be built with the temporal noisy adder by Heckerman [24]. The BN model of the noisy adder is a random variable representing a counter and a probability distribution that defines the likelihood of observing a certain count.…”
Section: Introductionmentioning
confidence: 99%